Women Representatives in Britain, France, and the United States - Applewhite, Harriet Branson (Palgrave Macmillan, 2015)
"This book compares British, French, and American legislative debates on woman suffrage and women's rights. Beginning with an analysis of Tocqueville and J.S. Mill on the impact of suffrage, the book continues with analysis of floor debates, comparing gender style, the French on parity and the Americans on the ERA and concluding with modern debates"–
Keywords: France; Women; France; Women legislators; Great Britain; Women; Great Britain; Women legislators; History; Women; Suffrage; United States; United States; Women legislators; Women; dept.psc; faculty_collection